Analisa Tingkat Resiko Pada Proyek Pembangunan Pergantian Sei. Singgalang Kabupaten Kampar - Saputra, Ramadhan; Setiawan, Beny; Sari, Resy Kumala; Adeswastoto, Hanantatur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The bridge replacement construction project involves numerous hazards that workers must bear, such as falling from heights, getting caught or trapped, being struck by materials, and others. After conducting an observation of the issues present in the Sei. Singgalang Bridge replacement project in Kampar Regency, it was found that many workers do not comply with safety regulations, such as not using Personal Protective Equipment (PPE). This poses a significant danger to the workers, considering that the work is carried out at elevated heights. Thus, a hazard assessment is necessary to identify the risks associated with the project. The Hazard Identification Risk Assessment Risk Control (HIRARC) methodology was chosen to be this assessment. HIRARC allows for evaluating hazards in each subtask and obtaining ratings for each identified risk. Based on Severity Index results, out of the 15 identified hazards, there are risks with a risk level exceeding 80%, falling under the category of Very High (VH) risk. The matrix table displays 11 risks with a scale of 25, 3 risks with a scale of 20, and 1 risk with a scale of 16 among all identified hazards. Consequently, it can be concluded that the risks in this project are categorized as high-risk hazards, and measures need to be implemented to control the identified risks. This can be achieved through elimination, substitution, engineering controls, administrative controls, and the use of appropriate PPE according to the hazards present at each workstation.